Caracterização química elementar de biomassa lignocelulósica, biochar e bio-óleo - Waechter, Samuel Rodrigo (2023)
In this work, sample preparation methods for the digestion of lignocellulosic biomass as well as biochar and bio-oil were developed for further elemental determination. For lignocellulosic biomass, the microwave assisted digestion in single reaction chamber (MAD-SRC) adapting the procedures of the EN ISO 16967 standard and addition to microwave-induced combustion (MIC), adapting the procedures from the EN ISO 16994 standard were used. For the biochar, the MAD-SRC method adapted from the EN ISO 16967 standard was used. For bio-oil digestion, the MAD-SRC method was developed. The determination of Al, Ba, Ca, Cl, Cu, Fe, K, Mg, Mn, Na, P, S, Si, Sr, Ti and Zn in the digests of lignocellulosic biomass and biochar (except for Cl) was carried out by inductively coupled plasma optical emission spectrometry (ICP OES). Chlorine determination in biochar was performed according to the ASTM D6721-01 by using the elemental analyzer Multi EA 5000. The determination of Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Mo, Na, Ni, P, Pb, Sn, S, Sr, Si, Ti, V and Zn in bio-oil digests was carried out using the inductively coupled plasma mass spectrometry (ICP-MS) and ICP OES. The accuracy of sample preparation methods, as well as for the elemental analyzer Multi EA 5000 was evaluated by using certified reference materials (CRM) with similar matrices, by results comparison with those after digestion by different methods and/or by recovery tests. The limits of quantification achieved for the determination of the evaluated analytes were considered satisfactory for the lignocellulosic biomass, biochar and bio-oil analysis. Finally, protocols of analysis for elemental determination of lignocellulosic biomass, biochar and bio-oil were proposed. These protocols were applied for the analysis of 9 samples of lignocellulosic biomass, 10 samples of biochar and 3 samples of bio-oil (including their respective aqueous and non-aqueous phases). For the lignocellulosic biomass and biochar, a high concentration of ash-forming elements (e.g. Al, Ca, Cl, Fe, K, Mg, P, S and Si) was observed. Regarding to the bio-oil samples, the S concentration was about 110 µg g-¹ , while for the other analytes the concentration was lower than 100 µg g-¹ . The additional studies show that the analytes distribution in fast pyrolysis products of the pine lignocellulosic biomass occurs mainly in biochar. Moreover, it was observed that the analytes distribution in the aqueous and nonaqueous phase is similar for the analyzed samples, where elements as Ca, K, Mg and Mn are mainly in the aqueous phase, while Al, Ba, Fe, Ni and S are mainly in non-aqueous phase.